Cyanocobalamin Ultraflexible Lipid Vesicles: Characterization and In Vitro Evaluation of Drug-Skin Depth Profiles - Antonio José Guillot; Enrique Jornet-Mollá; Natalia Landsberg; Carmen Milián-Guimerá; M. Carmen Montesinos; Teresa M. Garrigues; Ana Melero (MDPI AG, 2021)
Atopic dermatitis (AD) and psoriasis are the most common chronic inflammatory skin disorders, which importantly affect the quality of life of patients who suffer them. Among other causes, nitric oxide has been reported as part of the triggering factors in the pathogenesis of both conditions. Cyanocobalamin (vitamin B12) has shown efficacy as a nitric oxide scavenger and some clinical trials have given positive outcomes in its use for treating skin pathologies. Passive skin diffusion is possible only for drugs with low molecular weights and intermediate lipophilicity. Unfortunately, the molecular weight and hydrophilicity of vitamin B12 do not predict its effective diffusion through the skin. The aim of this work was to design new lipid vesicles to encapsulate the vitamin B12 to enhance its skin penetration. Nine prototypes of vesicles were generated and characterized in terms of size, polydispersity, surface charge, drug encapsulation, flexibility, and stability with positive results. Additionally, their ability to release the drug content in a controlled manner was demonstrated. Finally, we found that these lipid vesicle formulations facilitated the penetration of cyanocobalamin to the deeper layers of the skin. The present work shows a promising system to effectively administer vitamin B12 topically, which could be of interest in the treatment of skin diseases such as AD and psoriasis.